Nexus between Governance and Sustainable Development in Developing Countries: A Simultaneous Approach - Siddiqa, Ayesha; Danish, Muhammad Hassan; Ashfaq, Muhammad (ETIKONOMI, 2025)
Research Originality: The present research contributes a novel task in examining the simultaneous relationship between governance and sustainable development (SD), aiming to capture the endogenous relationship between these two concepts. Research Objectives: This study examines the relationship between governance and sustainable development in 59 developing countries, utilizing annual data from 2006 to 2022. Research Method: The study employs panel Generalized Methods of Moment (GMM) and panel three-stage least squares (3SLS) techniques by using STATA 17. Data for this study is extracted from the World Development Indicators (WDI), International Financial Statistics, and World Governance Indicators. Empirical Results:  The findings indicate that governance, tax-to-GDP ratio, and financial development are positively related to SD. Moreover, SD also has a positive impact on governance in developing countries. Control variables, including the misery index and population, are negatively related to governance. Implications: The study offers policy recommendations to enhance transparency and government quality, which are integrated into the development process to reduce social disparities, mitigate environmental challenges, foster economic growth, and ensure the well-being of citizens. JEL Classification: F63, O16, Q01